2012
DOI: 10.2307/41703468
|View full text |Cite
|
Sign up to set email alerts
|

Enacting Clan Control in Complex IT Projects: A Social Capital Perspective

Abstract: The information technology project control literature has documented that clan control is often essential in complex multistakeholder projects for project success. However, instituting clan control in such conditions is challenging as people come to a project with diverse skills and backgrounds. There is often insufficient time for clan control to develop naturally. This paper investigates the question, "How can clan control be enacted in complex IT projects?" Recognizing social capital as a resource, we conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
119
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(130 citation statements)
references
References 82 publications
2
119
1
3
Order By: Relevance
“…Informal control promotion in IS offshoring projects Previous research has found that deployment of clan control fosters social cohesion and norm-based alignment of behaviours in (IS) project teams, facilitating project team success (Kirsch 1996(Kirsch , 1997Ouchi, 1980;Chua et al, 2012). Recent studies show that clan control can be successfully promoted not only in internal project contexts (Kirsch et al, 2010) but also in distant offshore settings (Persson et al, 2012).…”
Section: Hypotheses Developmentmentioning
confidence: 94%
See 3 more Smart Citations
“…Informal control promotion in IS offshoring projects Previous research has found that deployment of clan control fosters social cohesion and norm-based alignment of behaviours in (IS) project teams, facilitating project team success (Kirsch 1996(Kirsch , 1997Ouchi, 1980;Chua et al, 2012). Recent studies show that clan control can be successfully promoted not only in internal project contexts (Kirsch et al, 2010) but also in distant offshore settings (Persson et al, 2012).…”
Section: Hypotheses Developmentmentioning
confidence: 94%
“…These common IS project attributes are enhanced in the context of IS offshoring projects, which require cooperation between two distant organizations, and where complexity and uncertainty on both sides of the relationship are channelled through the client-vendor interface. Here, clan control can be particularly useful, partly because it facilitates cooperation and partly because clan control improves control adaptiveness, thus positively affecting project performance (Kirsch et al, 2002;Kirsch, 2004;Kohli & Kettinger, 2004;Chua et al, 2012). First, successfully promoted clan control between the client and vendor managers fosters continuous communication and bilateral knowledge transfer (Kirsch et al, 2010).…”
Section: Informal Control Effectiveness In Is Offshoring Projectsmentioning
confidence: 95%
See 2 more Smart Citations
“…A review of journal publications 2011 and 2012 reveals a number of case studies that draw attention to their neglect. For example, [1] discusses the importance of 'collective mindfulness' including "continuous learning from failures and the willingness to consider alternative perspectives in developing complex sociotechnical systems", [2] discuss how 'clan control' is "often essential in complex multistakeholder projects for project success", [3] discusses "different societal and organizational cultures" in their action research projects, [4] draws attention to the importance of strategic alignment in their field study in 24 large Canadian companies: "the alignment of the IT function with business objectives must not only be understood, but constantly renewed and adjusted", [5] find that in their cases "rule-bending (rule-breaking) and partial-use (totally bypassing systems) can be behaviors that are primarily associated with work ethos and material constraints of work", [6] advises that "managers should plan strategies to construct and present an appropriate image of the system, in which stakeholders perceive that it meets their needs", and finally [7] reports on "influence of supervisors, performance evaluation schemes, intrinsic motivation, and perceived usefulness" as key drivers to success" in their case studies,…”
Section: Introductionmentioning
confidence: 99%